Drugs against metabolic diseases as potential senotherapeutics for aging-related respiratory diseases - Matsubayashi, Sachi; Ito, Saburo; Araya, Jun; Kuwano, Kazuyoshi (Frontiers in Endocrinology, 2023)
Recent advances in aging research have provided novel insights for the development of senotherapy, which utilizes cellular senescence as a therapeutic target. Cellular senescence is involved in the pathogenesis of various chronic diseases, including metabolic and respiratory diseases. Senotherapy is a potential therapeutic strategy for aging-related pathologies. Senotherapy can be classified into senolytics (induce cell death in senescent cells) and senomorphics (ameliorate the adverse effects of senescent cells represented by the senescence-associated secretory phenotype). Although the precise mechanism has not been elucidated, various drugs against metabolic diseases may function as senotherapeutics, which has piqued the interest of the scientific community. Cellular senescence is involved in the pathogenesis of chronic obstructive pulmonary disease (COPD) and idiopathic pulmonary fibrosis (IPF), which are aging-related respiratory diseases. Large-scale observational studies have reported that several drugs, such as metformin and statins, may ameliorate the progression of COPD and IPF. Recent studies have reported that drugs against metabolic diseases may exert a pharmacological effect on aging-related respiratory diseases that can be different from their original effect on metabolic diseases. However, high non-physiological concentrations are needed to determine the efficacy of these drugs under experimental conditions. Inhalation therapy may increase the local concentration of drugs in the lungs without exerting systemic adverse effects. Thus, the clinical application of drugs against metabolic diseases, especially through an inhalation treatment modality, can be a novel therapeutic approach for aging-related respiratory diseases. This review summarizes and discusses accumulating evidence on the mechanisms of aging, as well as on cellular senescence and senotherapeutics, including drugs against metabolic diseases. We propose a developmental strategy for a senotherapeutic approach for aging-related respiratory diseases with a special focus on COPD and IPF.